Analisis Nilai Overall Equipment Effectiveness Pada Mesin Wheeloader Liugong CLG-856 - Suparmanto Suparmanto; Adi Nugroho (LPPM Universitas Putera Batam, 2019)
Work measurement system is very important for the company, it aims to know whether or not achieved the target company. The use of the tool can only be repaired and controlled properly if the right performance measurement system is used, to know the value of a machine or equipment effectiveness it is necessary to use a method of Overall Equipment Effectiveness (OEE), to obtain the OEE value required calculation 3 (three) Availability Ratio, Performance effeciency, Rate ofQuality. The research was conducted on the Wheel Loader CLG-856 engine. The data used in this study consisted of data for one year. OEE calculation results from January 2016 - December 2016. The average value of Availability wheel loader no 16 from january 2016-december 2016 is 87.10%, Value Performance efficiency wheel loader no 16 from January 2016-December 2016 is above the value Ideal> 95%, Rate of Quality wheel loader no 16 from January 2016 - December 2016 is above ideal value> 99%, and OEE indicates that it is still below ideal value> 85%, where the average value of OEE is 84 , 73%, and the value is categorized acceptablebut needs to be over 85% improvement and move towardswordclass.